1986
DOI: 10.1152/jn.1986.55.4.826
|View full text |Cite
|
Sign up to set email alerts
|

Role of corticobulbar projection neurons in cortically induced rhythmical masticatory jaw-opening movement in the guinea pig

Abstract: The role of the pyramidal tract (PT) in the induction of the rhythmical masticatory activity (RMA) of the anterior digastric motoneurons by repetitive stimulation of the cortical masticatory area (CMA) was studied in the ketamine-anesthetized guinea pig. The coronal section of the medial brain stem at the pontine level did not show any effect on the cortically induced RMA in the digastric EMG, as long as the majority of the PT fibers was spared of the section. In contrast, unilateral section of the PT at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…These neurons are thought to activate another group lying more dorsally in the same region. In the original model, the latter group, which fires rhythmically during fictive mastication, were the premotoneurons that controlled trigeminal motoneurons (Nozaki et al, 1986b). However, projections from this area to N Vmt are very sparse (Travers and Norgren, 1983;Landgren et al, 1986), so a relay in caudal N reticularis parvocellularis was added (Nozaki et al, 1993;Nakamura and Katakura, 1995).…”
Section: Do Rpc-␣ and Nvspo-␥ Neurons Play Different Roles In Masticamentioning
confidence: 99%
“…These neurons are thought to activate another group lying more dorsally in the same region. In the original model, the latter group, which fires rhythmically during fictive mastication, were the premotoneurons that controlled trigeminal motoneurons (Nozaki et al, 1986b). However, projections from this area to N Vmt are very sparse (Travers and Norgren, 1983;Landgren et al, 1986), so a relay in caudal N reticularis parvocellularis was added (Nozaki et al, 1993;Nakamura and Katakura, 1995).…”
Section: Do Rpc-␣ and Nvspo-␥ Neurons Play Different Roles In Masticamentioning
confidence: 99%
“…On the one hand, the heptapeptide participates in this process by directly acting on the central machinery for circulatory control [12-18, 20, 21 ]. On the other, it also influences cardiovas cular functions by affecting fluid volume, and 68 Y ang/Kuo/Chan/Chan Neurobiology of Central Angiotensin III and Dipsogenesis hence cardiac output, via regulation of water homeostasis. The maintenance of water homeostasis is of course one of the essential physiologic re quirements for the survival of terrestrial ani mals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on latency data from electrophysiologic studies, Lowe [56] proposed that craniohypoglossal reflexes are multisynaptic, and may involve relay neurons whose locations are within the brain stem. Although anatomic evidence [57,58] implicates the lat eral reticular formation (chiefly nucleus reti cularis parvocellularis) as containing such re- 66 Yang/Kuo/Chan/Chan Neurobiology of Central Angiotensin III and Dipsogcncsis As one of the major reticular nuclei in the medulla oblongata, the nucleus reticularis gigantocellularis (NRGC) is involved in both the processing of sensory information [59][60][61][62] and control of postural muscle tone [63][64][65][66], F.lectrophysiologic evidence also suggests that the NRGC participates in the regulation of cortically induced rhythmical masticatory jaw-opening movement in the guinea pig [67,68], Suzuki and Siegel [69] reported that a small number of cells in the medial reticular formation, including the NRGC, change their discharge rates in relation to tongue move ment. They suggest that these neurons may be involved in tongue-jaw coordination during mastication, licking and grooming in the un anesthetized cat.…”
Section: Nucleus Reticularis Gigantocelluiaris Hypoglossal Nucleus Amentioning
confidence: 99%
“…The lateral pterygoid and suprahyoid (SH; anterior belly of the digastric, geniohyoid and mylohyoid) muscles constitute the jaw opening muscles (or jaw openers), while the temporalis, masseter (Mass) and medial pterygoid muscles serve as the jaw closing muscles (or jaw closers). Chewing movements, which usually begin with jaw opening and are followed by jaw closing, have been noted among many mammalian species, including humans [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Two groups of nuclei, the paragigantocellular and gigantocellular reticular nuclei, and the medial bulbar reticular formation, located in the region of the medulla oblongata, are believed to play essential roles in the central pattern generator that controls the basic chewing rhythm [1][2][3]. Neurons of either or both nucleus groups send action potentials, via the parvocellular reticular nucleus, to the jaw opening and closing motoneurons, innervating the muscles responsible for chewing movement [4].…”
Section: Introductionmentioning
confidence: 99%